Dynamic conceptions of plurilingual and intercultural competence in the multilingual environment of Luxembourg. Issue 3 (3rd July 2019) - Stratilaki-Klein, Sofia
ABSTRACT: Contemporary education systems, particularly in European societies, are characterized by different forms of plurality: plurality of cultural references, in terms of values and principles, languages and visions of multilingualism. In this article, we argue that these different forms of plurality are important in many respects for teachers and students in the multilingual environment of the University of Luxembourg, as both social actors have a complex experience of language forms and uses. Even if this experience naturally differs from one social actor to another, we try to gain a more comprehensive understanding of the perceptions of plurilingual and intercultural competence, professional identity and teaching practices of a group of students and teachers. The plurilingual speaker is comprehended as a social actor, whose resources constitute linguistic, symbolic and cultural capital, and take different values in different contexts. Influential concepts are discussed in terms of their significance for a reorientation of multilingual education.